2015
DOI: 10.4172/2167-0250.1000126
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA Fragmentation in Saudi Infertile Men with Normal Standard Semen Parameters

Abstract: Almost 15% of infertile males have normal semen parameters and DNA Fragmentation Index (DFI) could be reasonably a valued tool for fertility extrapolation than the conventional semen analysis. To the best of our knowledge, this is the first study to assess the prevalence of high DFI in Saudi infertile men with normal standard semen parameters in order to support the generalizability about sperm DFI as a marker of male infertility. A total of 79 infertile men with normal semen standards were identified (study g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…About 15% of infertile Saudi men had normal semen parameters despite high DFI; therefore, testing DFI in addition to other semen parameters is beneficial [ 38 ] as the DFI evaluation may reveal a hidden abnormality in apparently normal sperm parameters [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…About 15% of infertile Saudi men had normal semen parameters despite high DFI; therefore, testing DFI in addition to other semen parameters is beneficial [ 38 ] as the DFI evaluation may reveal a hidden abnormality in apparently normal sperm parameters [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that even among men with normal semen analysis parameters, there are cases of advanced SDF. 16 …”
Section: Introductionmentioning
confidence: 99%
“…However, the CASA results are susceptible to being compromised in low and high-concentration specimens, especially for morphological results, due to the heterogeneity between shapes of sperm either in one sample or across multiple samples from one subject [ 6 ]. Despite the strict criteria in the latest WHO laboratory manual for normal semen examination and evaluation [ 7 ], around 15% of infertile men were still diagnosed with normal semen [ 8 ]. By contrast, a positive correlation between sperm DNA fragmentation and reduced male fertility, even impaired offspring fertility, has been confirmed [ 9 ], in which the sperm DNA fragmentation index was recognized as a promising detection marker for male infertility diagnosis.…”
Section: Introductionmentioning
confidence: 99%